Forum for injection techniques, India: The first Indian recommendations for best practice in insulin injection technique - Sanjay Kalra; Yatan Pal Singh Balhara; Manash P Baruah; Manoj Chadha; Hemraj B Chandalia; Subhankar Chowdhury; K M Prasanna Kumar; Sonal Modi; Shailesh Pitale; Rishi Shukla; Rakesh Sahay; Annamalai Sundaram; et al. (Indian Journal of Endocrinology and Metabolism, 2012)
Advances in the treatment of diabetes have led to an increase in the number of injectable therapies, such as human insulin, insulin analogues, and glucagon-like peptide-1 analogues. The efficacy of injection therapy in diabetes depends on correct injection technique, among many other factors. Good injection technique is vital in achieving glycemic control and thus preventing complications of diabetes. From the patients′ and health-care providers′ perspective, it is essential to have guidelines to understand injections and injection techniques. The abridged version of the First Indian Insulin Injection technique guidelines developed by the Forum for Injection Technique (FIT) India presented here acknowledge good insulin injection techniques and provide evidence-based recommendations to assist diabetes care providers in improving their clinical practice.